2017
DOI: 10.1016/j.reprotox.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported mobile phone use and semen parameters among men from a fertility clinic

Abstract: There is increasing concern that use of mobile phones, a source of low-level radio-frequency electromagnetic fields, may be associated with poor semen quality, but the epidemiologic evidence is limited and conflicting. The relationship between mobile phone use patterns and markers of semen quality was explored in a longitudinal cohort study of 153 men that attended an academic fertility clinic in Boston, Massachusetts. Information on mobile phone use duration, headset or earpiece use, and the body location in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…Among the lifestyle factors examined, physical activity had a positive effect on sperm concentration, while a BMI ≥35 kg/m 2 was associated with lower total sperm count (Chavarro, et al, 2010). We found no association between mobile phone use and semen parameters in this cohort (Lewis, et al, 2017).…”
Section: Resultscontrasting
confidence: 65%
“…Among the lifestyle factors examined, physical activity had a positive effect on sperm concentration, while a BMI ≥35 kg/m 2 was associated with lower total sperm count (Chavarro, et al, 2010). We found no association between mobile phone use and semen parameters in this cohort (Lewis, et al, 2017).…”
Section: Resultscontrasting
confidence: 65%
“…However, there is much less known about the beneficial effects of EMFs exposure to the reproductive performance and the semen quality [51–57]. Other reports also revealed that the direct exposure of sperm to magnetic or electromagnetic fields may have the detrimental effects on the sperm [52, 5861]. It seems that the direct exposure to either EMF or ELEF damages the sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Semen collection and analysis have been previously described (Meeker et al , 2006; Lewis et al , 2017). Briefly, men abstained from ejaculation for 48 hours prior to sample collection into plastic specimen cup.…”
Section: Methodsmentioning
confidence: 99%